Pelatihan Metode Pengajaran Untuk Meningkatkan Partisipasi Orang Tua Selama Pembelajaran Daring: Indonesia - Ahadiati, Lifthya; Habibi, Muhammad Mizan; Fatimah, Malida (UII, 2024)
Parents play an important role in the process of children’s development, including in the educational process. The pandemic situation that makes children carry out the learning process from home has made the role of parents even more significant. The lack of skills in accompanying the online learning process makes it difficult for parents to show a supportive parenting attitude for the child. Training on effective learning methods and supportive care for children has proven to be able to significantly improve the skills of parents in accompanying the online learning process. The training was delivered in several sessions ranging from initial assessment, providing training in the form of lectures and role play, posttests, to follow-up in the form of focused group discussions with teachers. Through the training, parents' understanding of effective learning methods increased significantly, reaching 62% of participants. This training has also been shown to be able to significantly improve parents' understanding in implementing supportive parenting. Furthermore, schools can also develop varied learning methods such as project-based learning during a pandemic to make it easier for students to understand the material while increasing interaction between parents and children.